Self-Tuning Fuzzy Based PI Controller for DFIM Powered by Two Matrix Converters - Abdelhakim Alalei; Abdeldjebar Hazzab; Ali Nesba (Institute of Advanced Engineering and Science, 2016)
This paper presents a study of the Doubly Fed Induction Machine (DFIM) powered by two matrix converters; one connected to the stator windings and the other connected to the rotor windings. First, the mathematical model of DFIM and those of the matrix converters are developed. Then, the vector control technique is applied to the DFIM. Fuzzy logic is used in order to automatically adjust the parameters of the PI controller. The performance of this structure under different operating conditions is studied. Particular interest is given to the robustness of the fuzzy logic based control. The operation of the DFIM under overload conditions is also examined. Simulation results obtained in MATLAB/Simulink environment are presented and discussed.